GaAsBi: From Molecular Beam Epitaxy Growth to Devices. Issue 2 (21st November 2021) - Richards, Robert D.; Bailey, Nicholas J.; Liu, Yuchen; Rockett, Thomas B. O.; Mohmad, Abdul R.
Abstract : GaAsBi has been researched as a candidate material for optoelectronic devices for around two decades. Bi‐induced localized states induce a rapid rising of the valence band edge through a band anticrossing interaction, which has a profound effect on the bandgap and the spin–orbit splitting. The band engineering possible, even with just a few percent bismuth, makes GaAsBi an attractive material for THz emitters, telecommunication lasers, and low noise photodetectors, among other devices. There has been substantial progress in some of these areas; however, progress toward many of the potential applications of GaAsBi has been hindered by device quality issues, brought about by the low substrate temperatures necessary for the growth of GaAsBi with sufficiently large Bi fractions. This review, presents an overview of the applications for which GaAsBi has been advocated and the key results in these areas. The molecular beam epitaxy growth and postgrowth processing of GaAsBi are then explored as well as the novel techniques that have been suggested to improve material quality. Abstract : This article reviews the recent progress of various GaAsBi‐based devices including detectors, photovoltaics, light‐emitting diodes, lasers, and terahertz emitters and the key results in these areas. Then, it presents the key challenges and limitations in GaAsBi growth, followed by recent molecular beam epitaxy growth techniques and postgrowth treatments to improve material quality and device performance.